Chiral Lewis Acid Catalyzed Reactions of α‐Diazoester Derivatives: Construction of Dimeric Polycyclic Compounds. Issue 49 (8th November 2018) - Tan, Fei; Liu, Xiaohua; Wang, Yan; Dong, Shunxi; Yu, Han; Feng, Xiaoming
Abstract: An unexpected homologation/dyotropic rearrangement/interconversion/[3+2] cycloaddition cascade reaction of α‐diazoester‐terminated N‐propyl‐substituted isatin derivatives was achieved in the presence of a chiral N, N′‐dioxide/Sc III catalyst. This catalytic manifold allows rapid construction of several classes of dimeric polycyclic compounds with good yields and high levels of diastereo‐ and enantioselectivity (up to 99 % ee ). Furthermore, macrocyclic dimers can be obtained by an intermolecular homologation process. Abstract : Simplifying complexity : A highly chemo‐ and enantioselective homologation/dyotropic transformation/interconversion/[3+2] cycloaddition cascade reaction of α‐diazoester‐terminated isatin derivatives with a three‐carbon tether was achieved. Dimeric polycyclic compounds containing multiple quaternary carbon centers were synthesized in one pot in the presence of a chiral N, N ′‐dioxide/Sc III catalyst.